2008
DOI: 10.1007/s11258-008-9557-0
|View full text |Cite
|
Sign up to set email alerts
|

Land-use history affects understorey plant species distributions in a large temperate-forest complex, Denmark

Abstract: In Europe, forests have been strongly influenced by human land-use for millennia. Here, we studied the importance of anthropogenic historical factors as determinants of understorey species distributions in a 967 ha Danish forest complex using 156 randomly placed 100-m 2 plots, 15 environmental, 9 spatial, and 5 historical variables, and principal components analysis (PCA), redundancy analysis (RDA) as well as indicator species analysis. The historical variables were status as ancient (1805 AD) high forest, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
1
14
0
1
Order By: Relevance
“…To sum up, our study shows a weak colonization credit in Mediterranean forests except for vertebrate‐dispersed woody species. Our study also shows contrasting woody species assembly in pre‐existing and recent Mediterranean forests, as also found in other forests (Hermy et al , Svenning et al ). Niche differentiation seems to play a key role in the Mediterranean woody community assembly.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To sum up, our study shows a weak colonization credit in Mediterranean forests except for vertebrate‐dispersed woody species. Our study also shows contrasting woody species assembly in pre‐existing and recent Mediterranean forests, as also found in other forests (Hermy et al , Svenning et al ). Niche differentiation seems to play a key role in the Mediterranean woody community assembly.…”
Section: Discussionsupporting
confidence: 80%
“…These results are quite surprising, as vertebrate‐dispersed species are presumed to achieve longer dispersal distances than non‐vertebrate‐dispersed ones (Tiffney and Mazer ). A number of previous studies have pointed out that species with good dispersal abilities are overrepresented in isolated patches (Kolb and Diekmann , Tremlovà and Münzbergovà ), particularly in recent forests (Flinn and Vellend , Svenning et al ). In the Mediterranean forests, Montoya et al () found that fragmented patches are mostly dominated by long‐distance vertebrate‐dispersed species.…”
Section: Discussionmentioning
confidence: 98%
“…; Svenning et al. ). The traits associated with core and peripheral species could also be explained by the remnant effect of former agricultural land use.…”
Section: Discussionmentioning
confidence: 97%
“…(ii) Principal coordinates of neighborhood matrix (PCNM) analysis based on the geographical distance was used to compute spatial variables (i.e., historic factors) representing geographical positions through the pcnm function in R package vegan (version 2.4‐2). The generated eigenvectors were considered as spatial variables (i.e., PCNMs), which could reflect unmeasured broadscale variation in the modern environment or historic factors, for example, natural dispersal‐generated patterns demonstrating internal local‐scale dispersal dynamics or regional‐scale migration history (Svenning, Baktoft, & Balslev, ). PCNMs with large eigenvalues and small code represent broadscale spatial pattern, while the smaller eigenvalues with large code represent fine‐scale patterns.…”
Section: Methodsmentioning
confidence: 99%